2019
DOI: 10.3390/molecules24162861
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Blood Proteins of a Ruthenium(II) Nitrofuryl Semicarbazone Complex: Effect on the Antitumoral Activity

Abstract: The steady rise in the cancer burden and grim statistics set a vital need for new therapeutic solutions. Given their high efficiency, metallodrugs are quite appealing in cancer chemotherapy. This work examined the anticancer activity of an anti-trypanosomal ruthenium-based compound bearing the 5-nitrofuryl pharmacophore, [RuII(dmso)2(5-nitro-2-furaldehyde semicarbazone)] (abbreviated as RuNTF; dmso is the dimethyl sulfoxide ligand). The cytotoxicity of RuNTF was evaluated in vitro against ovarian adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
(94 reference statements)
1
8
0
Order By: Relevance
“…There was a wave peak of BSA around 342 nm, which indicated that the tryptophan residue was the main source of BSA uorescence intensity. 27 When TA was added, the uorescence intensity of BSA decreased signicantly, which indicated that TA had a uorescence quenching effect on BSA, and the quenching effect had a strong dependence on the amount of TA added. In addition, the uorescence spectrum of BSA shied slightly red from 342.0 nm to 345.2 nm with a gradual increase in TA concentration.…”
Section: Resultsmentioning
confidence: 97%
“…There was a wave peak of BSA around 342 nm, which indicated that the tryptophan residue was the main source of BSA uorescence intensity. 27 When TA was added, the uorescence intensity of BSA decreased signicantly, which indicated that TA had a uorescence quenching effect on BSA, and the quenching effect had a strong dependence on the amount of TA added. In addition, the uorescence spectrum of BSA shied slightly red from 342.0 nm to 345.2 nm with a gradual increase in TA concentration.…”
Section: Resultsmentioning
confidence: 97%
“…[14] Albumin is the most abundant protein in the plasma [15] and the major nonspecific transporter in the blood. [16] The primary and secondary structures of albumin have been studied previously. [17] BSA is one of the most researched proteins, having activities that are critical for the disposition and transportation of a wide range of substances inside the body, including metal ions, medicines, hormones, steroids, and fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Common methods to investigate metallodrug–protein interactions are X-ray diffraction analysis, ,, electrospray ionization mass spectrometry (ESI-MS), , inductively coupled plasma optical emission spectrometry (ICP-OES) or mass spectrometry (ICP-MS), UV–vis spectroscopy, circular dichroism (CD) spectroscopy, tryptophan fluorescence spectroscopy, (nano)­liquid chromatography, , gel electrophoresis, capillary electrophoresis , or NMR. For emissive metallodrugs, the metal complex and hence its interaction with biomolecules can be imaged on gel electrophoresis or in cells by emission microscopy. , For the nonemissive metallodrugs considered here, however, this approach is ineffective. In organic chemical biology a well-developed method to visualize interaction between proteins and nonemissive organic inhibitors is based on bioorthogonal chemistry .…”
Section: Introductionmentioning
confidence: 99%